SISTEM INFORMASI ASET SEKOLAH BERBASIS WEBSITE PADA SMK NEGERI 4 BANDA ACEH - Nabila Razani; Khairan AR; Rahmat Musfikar (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Website-Based School Asset Information System is a system that provides reports on borrowing goods, condition of goods, number of goods and records of borrowing or transferring assets that are currently implementing a data processing system in the form of Microsoft Excel and also bookkeeping for recording borrowed goods. This can be very time consuming, effort and also costly. As technology develops, it is time to switch to manual methods of asset maintenance using technology, an Asset Information System must be developed so that assets are more easily monitored and so that if assets are lost or damaged it is easy to check them. The development of this system uses the UML (Unified Modeling Language) model, including use case diagrams, flowcharts and Table Relations. This research uses the R&D method and also uses the waterfall development method, PHP programming and MySQL database.